Improving the European input-output database for global trade analysis - José M. Rueda Cantuche; Tamás Révész; Antonio F. Amores; Agustín Velázquez; Marián Mráz; Emanuele Ferrari; Alfredo Mainar; Letizia Montinari; Bert Saveyn (Journal of Economic Structures, 2020)
There are increasing numbers of published articles in the field of input-output analysis and modelling that use the GTAP input-output database; particularly, in relation to the estimation of carbon, energy and water footprints and the analysis of global value chains and international trade. The policy relevance of those topics is also increasing, thus calling for consistently linking these databases with official statistics. Although, so far, GTAP has been using their own classification and reconciliation methods, this paper develops a new conversion method for the EU that guarantees that the EU-GTAP database respects the new statistical standards and Eurostat official statistics. We recommend for future updates, a shift of the current GTAP classification of industries to the new official standard classifications to which countries are progressively moving to. Otherwise, the lack of matching official data would jeopardize the usefulness of such database. This method can be extended to other similar input-output databases with different classification schemes from the original input data sources.
Keywords: 330; Input-output tables; European Union; GTAP; Supply and use tables